THE EFFECT OF ACCOUNTING COMPREHENSION LEVEL, IMPLEMENTATION OF SAK EMKM AND COMPETENCE OF HUMAN RESOURCES (HR) ON THE QUALITY OF MSME FINANCIAL STATEMENTS IN TRENGGALEK REGENCY - Rifkha Nur Jannah; Ruly Priantilianingtiasari (SEAN Institute, 2023)
The background in this study is the existence of economic policies in the State of Indonesia which are directed at achieving an increase in public welfare. So that it becomes one of the supports so that MSMEs are able to implement a healthy and stable financial system. The purpose of this study was to examine the effect of the level of accounting understanding, the application of SAK EMKM, and the competence of human resources (HR) on the quality of MSME financial reports in Trenggalek Regency. The method in this study is descriptive quantitative type, the number of samples obtained is 100 respondents, data collection techniques using questionnaires, data analysis techniques using SPSS 26 assistance through testing, namely the classical assumption test, multiple linear regression test, hypothesis testing and R2 determination coefficient test. The results of this study simultaneously in this study are, there is a significant influence on the level of accounting understanding, the application of SAK EMKM, and the competence of human resources (HR) on the quality of MSME financial reports in Trenggalek Regency.